A use of a composition comprising of acylated steryl glucoside in the manufacture of a product. - Ismail, Maznah; Imam, Umar Mustapha; Musa, Asma S. N. (2013)
The present invention relates to a use of a composition in the manufacture of a product for regulating a plurality of genes consisting of phosphoenolpyruvate carboxykinase-1, fructose-1, 6-bisphosphatase, xenobiotic metabolism, low-density lipoprotein receptor, apolipoprotein-A1, superoxide dismutase-2, and catalase, characterised in that: the composition comprising acylated steryl glucoside.